Cyber-Resilient Platform Requirements - england, paul; aigner, ronald; marochko, andrey; mattoon, dennis; spiger, rob; thom, stefan (2017)
This is a draft specification describing processor and/or platform technologies that provide a foundation for device vendors to build cyber-resilient systems. The technologies are general purpose and can be implemented by any platform, processor, or SoC, but a priority is to define technologies that are suitable for IoT devices. The mechanisms in this specification are well suited for constructing systems that meet the requirements of NIST SP-800-193 (DRAFT) “Platform Firmware Resiliency Guidelines.”